Authoritarian containment public security bureaus and Protestant house churches in urban China - Reny, Marie-Eve (New York, NY, United States of America Oxford University Press, 2018)
Explaining authoritarian containment -- Informal protestantism in China and local government toleration -- Why public security bureaus contain Protestant house churches -- Everyday forms of containment -- Containment and authoritarian regime resilience -- Containment across authoritarian landscapes
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Church and state -- China; House Churches -- Government policy -- China; Protestant Churches -- China; Authoritarianism -- China; Church and state -- China; House Churches -- Government policy -- China; Protestant Churches -- China; Authoritarianism -- China; Hochschulschrift